Connectivity index of infrastructural accessibility for disabilities in the city of Palembang - Yogie Ardiwinata; Maryono Maryono; Annisa Kurnia Shalihat (Program Pascasarjana Universitas Sriwijaya, 2019)
Accessibility is a major component in the physical planning of an area. Good physical planning must include important components including facilities for persons with disabilities to be used by all people. The downtown area of Palembang is a strategic area of Palembang city that needs to be assessed on the connectivity index. The research object used is public facilities that are used as connectivity between buildings. This assessment was carried out aiming to determine the completeness of existing facilities and the feasibility of accessibility between buildings. The assessment is carried out by identifying existing facilities and to determine the level of completeness of the facilities through the scoring method. The connectivity index analysis was carried out based on these results to determine the feasibility of the facility and the feasibility of accessibility in the region. The results obtained from the connectivity index analysis are the level of accessibility between buildings. The level of accessibility is carried out classification based on the connectivity index to determine the feasibility of accessibility between buildings. Based on these results, there are four feasibility classifications in the central area of Palembang. Two roads are categorised as very feasible, five roads are decent, five road segments are less feasible and one road is not feasible.